Famílias escravas no recôncavo da Guanabara : séculos XVII e XVIII - Demetrio, Denise Vieira (2008)
The thesis focuses on issues related to the slave family around Guanabara Bay from late the seventeenth century to early eighteenth century. The research is based on the documentation of two particular parishes (Santo Antonio de Jacutinga and Irajá) and two Jesuit s estates (Engenho Velho e São Cristóvão). The goal is to compare the slave family organization patterns within the ecclesiastical estates with those of the other estates to argue about the different networks involving slaves and members of the local elites (compadrio). The research strongly relies on ecclesiastical sources, in particular baptismal records to show how horizontal (within the local elite) and vertical (between masters and slaves) relationships allows the organization of social and religious networks according to the rules of the Ancient Regime. The documentation under analysis shows that, beyond the Catholic ritual the compadrio involving masters and godparents from the local elite was also a strategy to reinforce and improve social links among the elite itself.